(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2014)
The Umm Irna Formation, exposed along the eastern shore of the Dead Sea, has been the focus of intense palaeobotanical study, but more recently, it has been revealed that well-preserved palynological assemblages are also present. The age of the Umm Irna Formation is such that it provides a showcase for taxa from the Guadalupian (mid Permian) to Lopingian (late Permian) which are hard to find in the carbonate-dominated successions to the southeast in the Arabian Peninsula and elsewhere in the Middle East. In this paper distinctive taxa present in the Umm Irna Formation are described and illustrated, and surveyed for their stratigraphic occurrences, to consider their suitability for biozonal indices within the Guadalupian to early Lopingian. Two appear to be promising: Protohaploxypinus uttingii Stephenson and Filatoff, 2000 and Pretricolpipollenites bharadwajii Balme, 1970. The first is distinctive in that it is relatively small, has numerous, very narrow taenaie, and a shrunken intexinal corpus; the second has three narrow distal sulci. Both taxa may have first appearance levels within thePermianabove the base of the OSPZ6 palynological Biozone, and thus may be useful in the future for further biozonation.